PERANCANGAN BUKU POP-UP KESENIAN DONGKREK MADIUN MENGGUNAKAN TEKNIK PULL-TABS SEBAGAI UPAYA MENGENALKAN BUDAYA LOKAL KEPADA ANAK-ANAK - Hafizhuddin, Oni Nur; Riyanto, Darwin Yuwono; Hidayat, Wahyu (Jurnal Art Nouveau, 2017)
Dongkrek popularized in 1910 by Raden Bei Lo Prawirodipura who was a District Officer (post of village head level) in the area Caruban. Society at that time to hear the music of this form of musical art dongkrek 'dung' is derived from the drum or drums and the